Traffic system in Malaysia: The factors that influence traffic congestion in urban area - Zahari, Norshafarina; Aziz, Zulkufli (2012)
The focus of this paper is on traffic congestion in urban area such as Kuala Lumpur and Penang. Traffic system in Malaysia still in the low level.It is because Malaysia has a many barrier to be a good in traffic system likes other country.The factors that influence this condition occur is the attitude of the road users, service of public transport, high population and facilities.Besides that, if traffic congestion interminable occur it will give negative impact to environment and economic.Because of that, all party must involved and plays their own roles to reduce the congestion problems.